Application of Relaxation Techniques And Hypnobirthing Methodsto Reduce Anxiety During Birth in Novi lintas east district midwifery clinic Panyambungan District Christmas Mandailing Year 2024 - Nasution, Helmi Wardah; Desi, Ferika (Cattleya Darmaya Fortuna, 2024)
Handling anxiety in pregnant women during the birthing process can use pharmacological and non-pharmacological methods, one of which is the hypnobirthing method. Hypnobirthing during pregnancy and childbirth is a combination of the natural birth process with hypnosis therapy to build self-confidence, positive perception, reduce fear, anxiety and tension before childbirth, during labor and after childbirth. This study aims to determine the application of relaxation techniques and hypnobirthing methods to reduce anxiety levels during childbirth at the Novi Lintas Timur Midwife Clinic, Panyabungan District.Mandailing Natal Regency in 2024..The type of research used is descriptive research with a Pre-Experimental One-Group Pretest – Posttest Design approach. The population in the study were mothers who gave birth at the Novi midwife clinic. The sampling technique used Accidental Sampling with a sample size of 10 people. Data collection using primary and secondary data. Data analysis used the simultaneous F test with a significance level of F > 0.05). The results of the analysis show that there is an influence of the hypnobirthing method to reduce anxiety during childbirth with a value of P = 0.001 where P = <0.05. It is hoped that this research can provide information and input for health workers in order to develop the quality of services at the Novi Lintas Timur Midwife Clinic, Panyabungan District, Mandailing Natal Regency.